Experimental validation of OSNR enhancement utilizing hybrid Raman/Erbium fiber amplifiers - Ahmad, A.; Izyani, M.A.M.; Zamzuri, A.K.; Adikan, Faisal Rafiq Mahamd; Sheih, S.J.; Mahdi, M.A. (2005)
The impact of employing a hybrid Raman/Erbium-doped fiber amplifier (EDFA) in a transmission system is demonstrated by considering the optical signal-to-noise ratio (OSNR) performance. The gain flatness of hybrid Raman/EDFA is maintained below 1.2 dB from 1530 to 1565 nut through careful design of both amplifiers. The enhancement of OSNR is measured at around 5 dB, compared to the conventional EDFA approach with a 28-dB span loss. (c) 2005 Wiley Periodicals, Inc.